The Scourge of Religious Conflicts in Tunji Ogundimu’s Paradise at Night - Moussa, Sidi Chabi (European Scientific Journal, ESJ, 2020)
Religious conflicts have become a serious issue which undermines the African continent and which deserves close attention. So, Marx rightly claims that religion is the opium of the people. This research work aims at examining the scourge of religious conflicts in Tunji Ogundimu’s Paradise at Night. It also aims at reflecting on their manifestations and impact on the one hand and on religious and political leaders’ limits in their resolution on the other hand. The focus of this research work is limited to a critical appraisal of the novel under study with illustrations. The methodological approaches used in this paper are the phenomenological and descriptive approaches. Based on the example of Nigeria which is the setting of the novel, the findings of the study clearly show that religious conflicts expose innocent people to a lot of harm and that the adherents of the two major religions do not collaborate peacefully. This situation is deplorable insofar as it does not favour development. A country where religious conflicts prevail cannot enhance a lasting development because of their devastating effects. The paper recommends and concludes that Christians and Muslims should promote tolerance, peace and love rather than indulging in violence so that religious conflicts should be eradicated in Nigeria and in Africa at large.